Penerapan Kooperatif Tipe Jigsaw pada Pembelajaran Matematika Materi Bilangan Cacah di MI Al-Alif Darussalam Bekasi - Ginianisa Tri Sekar Wulan; Fadillah Prabowo; Subandriyo Subandriyo (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Mathematics learning on whole number topics in elementary education still faces various challenges, particularly low student participation and conceptual understanding due to teacher-centered instructional practices. This study aims to describe the implementation of the Jigsaw cooperative learning model in teaching whole numbers to third-grade students at an Islamic elementary school (Madrasah Ibtidaiyah) in Bekasi. The research employed a qualitative approach using a case study method. The participants consisted of one teacher and six students selected through purposive sampling. Data were collected through observations, interviews, and documentation and analyzed using the Miles and Huberman model. The findings revealed that the implementation of the Jigsaw cooperative learning model was carried out systematically through planning, implementation, and evaluation stages. The learning process involved the formation of home groups and expert groups, which encouraged interaction, collaboration, learning responsibility, and students’ confidence in explaining concepts to their peers. Although some students remained passive, the Jigsaw model successfully fostered a more active, collaborative, and student-centered learning environment.